Perbandingan Model Pembelajaran Koperatif Tipe CRC dan TTW pada Aktivitas Belajar Mahasiswa - Ani Interdiana Candra Sari; Rendika Vhalery (SAP (Susunan Artikel Pendidikan), 2021)
Learning activity is an important factor in the learning process that can reflect the motivation or desire of students to learn. However, the implementation does not go well. It is caused by problems such as students sitting more still and listening to lecturers' explanations. It will give a negative impact where students will become passive. The application of an appropriate learning model is one of the strategies in learning to increase student learning activities. One of the learning models that can be applied to improve learning activities is the cooperative learning model. There are many types of cooperative learning models including CIRC (Cooperative Integrated Reading Composition) and TTW (Think-Talk-Write). This research was an experimental study using a Completely Randomized Design that did not use a control class. Then it proceeded with comparative research that compared the cooperative learning models CIRC and TTW on student learning activities. Experimental class 1 applied the CIRC cooperative learning model and experimental class 2 applied the TTW cooperative learning model. The results showed that there was no difference in the average learning activity of students using the CIRC type of cooperative learning model, there was a difference in the average learning activity of students using the TTW type of cooperative learning model, there was no difference in using the CIRC and TTW cooperative learning models on student learning activities.